Cancer Susceptibility as a Cost of Reproduction and Contributor to Life History Evolution - Dujon, Antoine M.; Boutry, Justine; Tissot, Sophie; Lemaître, Jean-François; Boddy, Amy M.; Gérard, Anne-Lise; Alvergne, Alexandra; Arnal, Audrey; Vincze, Orsolya; Nicolas, Delphine; Giraudeau, Mathieu; Telonis-Scott, Marina; et al. (Frontiers in Ecology and Evolution, 2022)
Reproduction is one of the most energetically demanding life-history stages. As a result, breeding individuals often experience trade-offs, where energy is diverted away from maintenance (cell repair, immune function) towards reproduction. While it is increasingly acknowledged that oncogenic processes are omnipresent, evolving and opportunistic entities in the bodies of metazoans, the associations among reproductive activities, energy expenditure, and the dynamics of malignant cells have rarely been studied. Here, we review the diverse ways in which age-specific reproductive performance (e.g. reproductive ageing patterns) and cancer risks throughout the life course may be linked via trade-offs or other mechanisms, as well as discuss situations where trade-offs may not exist. We argue that the interactions between host–oncogenic processes should play a significant role in life-history theory, and suggest some avenues for future research.